(untitled) (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted to study the effect of different watering frequencies on body weight and feed intake of Surti goats during hot dry and hot humid season under intensive production system. Eighteen adult farm born dry non pregnant female Surti goats (20 - 30 kg) were divided randomly on the basis of body weight comprising of six animals in each treatment viz., T1: Control (watering thrice in a day), T2: (12 hrs watering interval – watering twice in a day) and T3: (24 hrs watering interval – watering once in a day). The body weight (kg) of experimental animals was comparable among treatment, season and period. The daily DMI (g/d) significantly (P < 0.05) influenced by different watering frequencies whereas, DMI (g/100 kg BW) and DMI (g/kg W0.75) did not differ significantly among treatment groups. The DMI (g/d) increased significantly (P < 0.05) on 2nd day of rehydration as compared to last day of dehydration in goats maintained at 24 hrs watering interval. However, DMI in terms of g/100 kg BW and g/kg W0.75 was comparable among treatment groups. The results indicated that the goats should be given ad lib water at least once in a day at the interval of 24 hrs.